Fluoxetine for reducing postoperative cognitive dysfunction in elderly patients after total knee replacement: study protocol for a single-centre, double-blind, randomised, parallel-group, superiority, placebo-controlled trial - Yusheng Yao; Hong Ye; Yushan Wu; Daoyi Lin; Lulu Yu; Jiaxin Chen (BMJ Open)
Introduction Postoperative cognitive dysfunction (POCD) is a common complication following major surgical procedures. The underlying pathophysiology is poorly understood, but the role of neuroinflammation is strongly implicated. Given the antineuroinflammatory and neuroprotective effects of fluoxetine, we hypothesise that fluoxetine may reduce the cumulative incidence of POCD in elderly patients undergoing total knee arthroplasty (TKA).Methods and analysis This is a prospective, randomised, double-blind, parallel-group, placebo-controlled, superiority trial. Five hundred elderly patients undergoing unilateral TKA will be randomly assigned to the fluoxetine and placebo groups. The fluoxetine group will receive fluoxetine 20 mg daily 8 weeks preoperatively, and the placebo group will receive placebo capsules daily 8 weeks preoperatively. The primary outcome is the cumulative incidence of POCD at 1 month postoperatively. The secondary outcomes include the occurrence of delirium, the area under the curve of the Numeric Rating Scale pain scores over time, and sleep disturbance. Data on all the results, risk factors and adverse events will also be collected and analysed.Ethics and dissemination The Fujian Provincial Hospital Ethics Board has approved the protocol for this trial (identifier number: K2021-01-009). All participants will be required to provide written informed consent before any protocol-specific procedures.Trial registration number ChiCTR2100050424.